IMPROVING STUDENTS’ READING COMPREHENSION USING VIP (VOCABULARY INVESTOR PACKAGE) MEDIA AT SMKN 1 BATU - Indah Dwi Wahyuni; Erythrina Crista Wijayanti (Fakultas Ilmu Budaya, Universitas Brawijaya, 2020)
One of main concerns of the most English as Foreign Language (EFL) teachers is how to assist the students to develop English language proficiency. In this regard, reading is considered as a crucial part of the EFL learning process. The major goal of teaching reading is students are able to recognize the words and convey the meaning of them. Vocabulary seems to gain far more attention as the students had difficulties of interpreting the words that interferes their reading comprehension. Given such limitation of the students’ competence, their motivation may become low. Having seen this phenomenon, the teacher should maximize opportunities for students to improve their reading comprehension as well as their motivation. To this end, this research investigates the implementation of VIP (Vocabulary Investor Package) Media to enhance students’ reading comprehension. The research conducted Classroom Action Research (CAR) by employing 2 cycles to 28 students of twelve grade at SMKN 1 Batu. Accordingly, the procedures included planning, implementing, observing, and reflecting. The results show that (1) the highest score in cycle 2 was higher than the highest score in cycle 1; (2) the lowest score in cycle1 increased compared to cycle 1; (3) the average score was better than in cycle 1; (4) the percentage of students who achieved the minimum criterion (KKM) in cycle 2 was improved rather than in cycle 1; and (5) the percentage of students who did not reached KKM was decreased compared to cycle 1. Therefore, the use of VIP (Vocabulary Investor Package) Media successfully improves students’ reading comprehension. For the effective implementation, this suggests that applying VIP media to the other skills is highly required One of main concerns of the most English as Foreign Language (EFL) teachers is how to assist the students to develop English language proficiency. In this regard, reading is considered as a crucial part of the EFL learning process. The major goal of teaching reading is students are able to recognize the words and convey the meaning of them. Vocabulary seems to gain far more attention as the students had difficulties of interpreting the words that interferes their reading comprehension. Given such limitation of the students’ competence, their motivation may become low. Having seen this phenomenon, the teacher should maximize opportunities for students to improve their reading comprehension as well as their motivation. To this end, this research investigates the implementation of VIP (Vocabulary Investor Package) Media to enhance students’ reading comprehension. The research conducted Classroom Action Research (CAR) by employing 2 cycles to 28 students of twelve grade at SMKN 1 Batu. Accordingly, the procedures included planning, implementing, observing, and reflecting. The results show that (1) the highest score in cycle 2 was higher than the highest score in cycle 1; (2) the lowest score in cycle1 increased compared to cycle 1; (3) the average score was better than in cycle 1; (4) the percentage of students who achieved the minimum criterion (KKM) in cycle 2 was improved rather than in cycle 1; and (5) the percentage of students who did not reached KKM was decreased compared to cycle 1. Therefore, the use of VIP (Vocabulary Investor Package) Media successfully improves students’ reading comprehension. For the effective implementation, this suggests that applying VIP media to the other skills is highly required.